2023
DOI: 10.7759/cureus.33887
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Outcomes Among Pregnant Women Diagnosed With COVID-19

Abstract: Background: COVID-19 has the potential development of negative maternal outcomes for pregnant women. The risk of contracting COVID-19 is high as pregnancy alters the maternal immune system. Therefore, this study aims to assess maternal outcomes among pregnant women with COVID-19 in the Kingdom of Saudi Arabia.Methods: A retrospective study was conducted in three hospitals during the pandemic over four months, from the beginning of December 2019 until the end of March 2020. Data was collected using a structured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The course of the illness and neonatal outcome were investigated in a retrospective study carried out in the Hubei province, which included 16 pregnant women with COVID-19 infection and 45 pregnant women without COVID-19 who underwent C-section. In the events of fetal distress, meconium-stained amniotic fluid, premature delivery, and neonatal hypoxia, no notable differences were discovered and the neonates had no signs of infection [15] . Recent studies have reported the possibility of in utero COVID-19 transmission by measurement of fetal IgM blood level [16,17] .…”
Section: Discussionmentioning
confidence: 95%
“…The course of the illness and neonatal outcome were investigated in a retrospective study carried out in the Hubei province, which included 16 pregnant women with COVID-19 infection and 45 pregnant women without COVID-19 who underwent C-section. In the events of fetal distress, meconium-stained amniotic fluid, premature delivery, and neonatal hypoxia, no notable differences were discovered and the neonates had no signs of infection [15] . Recent studies have reported the possibility of in utero COVID-19 transmission by measurement of fetal IgM blood level [16,17] .…”
Section: Discussionmentioning
confidence: 95%
“…The observed adverse pregnancy outcomes were premature delivery (36.5%), fetal distress (20.7%), preeclampsia (2.4%), eclampsia (1.2%), and three maternal deaths. [ 22 ] In another analysis of 50 deliveries of COVID-infected mothers, there were a 94% cesarean rate and 35% preterm birth. [ 23 ] Our assessment revealed 9.61% miscarriage, 26.9% preterm delivery, 17.3% pre-eclampsia/eclampsia, 21.16% cesarean rate, and two maternal deaths.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unknown how COVID-19 would affect fetal respiratory failure, intrauterine fetal death, premature birth, or abortion. 13…”
Section: Effects Of Covid-19 On Pregnancymentioning
confidence: 99%